Evil, Barbarism and Empire
X, 290 p.
Keywords: Evil and barbarism continue to be associated with the totalitarian 'extremes' of twentieth-century Europe. Addressing domestic and imperial conflicts in modern Britain and beyond, as well as varied forms of representation, this volume explores the inter-relations of evil, atrocity and civilizational prejudice within liberal cultures of governance.